E-commerce and entrepreneurship - Butler, John, 1932- (Emerald Publishing Limited : Information Age Publishing, 2001)
Enthusiasm for e-commerce and the Internet has seen wide fluctuations, as the price of Internet and e-commerce firms' stock first increased and then declined dramatically. Business schools rushed to develop new courses related to electronic commerce to satisfy student demand, possibly because some saw this as a route to riches. There was also an increase in applied literature, which was to satisfy the demand for information on how to compete in this new environment, or on how to exploit the funds that appeared to be available for equity investments in these new ventures. The world of E-business is exciting, especially the prospect of making a lot of money. However, the degree to which e-commerce is linked to entrepreneurship in the longer term provides the focus for this volume. As with other new technologies such as the telephone, radio, television, and computer, growth was rapid in the initial stages of this technology. However, the degree to which the Internet and e-commerce will alter our theoretical perspectives on entrepreneurship has yet to be fully analyzed. This volume attempts to take a initial step by examining the intersection of e-commerce and entrepreneurship.
Keywords: Electronic commerce.; Entrepreneurship.; Business & Economics -- E-Commerce -- Small Business.; E-commerce: business aspects.; Small businesses and self-employment.; elektronické knihy; electronic books